Extrinsic evaluation through interconsistency in the catalogs of university libraries in the brazilian amazon: Ufpa, ufopa, ifpa and ufra - De Sousa, Letícia Lima; Barros, Thiago Henrique Bragato [UNESP]; Redigolo, Franciele Marques [UNESP]; Fujita, Mariângela Spotti Lopes (Universidade Federal de Santa Catarina (UFSC), 2020)
Objective: To analyze the consistency of indexing in online catalogs of BUs at the State University of Pará (UEPA), Federal University of Western Pará (UFOPA), Federal University of Pará (UFPA), Federal University of the South and Southeast of Pará (UNIFESSPA ), Federal Institute of Pará (IFPA) and Federal Rural University of the Amazon (UFRA). Method: Measure the degree of consistency between records using extrinsic evaluation through interconsistency in online catalogs. The rigid and relaxed consistency index between the records was calculated using the consistency equation adapted by Gil Leiva (2008), using Hooper’s formula (1965), and readapted in the present study to cover a sample of 10 tests obtained in the catalogs of the 6 BUs analyzed. Result: The rigid consistency index is low in relation to the relaxed consistency index that presented higher values, since the rigid consistency index has an interval that varies from 5.83 to 3.33. The relaxed consistency index, on the other hand, showed greater variation with an interval of 33.5 to 19.5. It verifies that the rigid consistency index has an average of 24.8 and the relaxed consistency index has an average of 24.05%. Conclusions: The cataloging of subjects at times presents concordant and divergent terms in the online catalogs of BUs. The variation in the attribution of terms between the indexers is due to the lack of a formal indexation policy. It verifies the validity of the extrinsic evaluation through interconsistency to check the degree of consistency of the records.
Avaliação Extrínseca Mediante A Interconsistência Nos Catálogos Das Bibliotecas Universitárias Da Amazônia Brasileira: Ufpa, Ufopa, Ifpa E Ufra
Keywords: Evaluation of interconsistency; Indexing; Online catalogs; Relaxed content; Rigid index